2017
DOI: 10.1016/j.expneurol.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Early-life febrile seizures worsen adult phenotypes in Scn1a mutants

Abstract: Mutations in the voltage-gated sodium channel (VGSC) gene SCN1A, encoding the Nav1.1 channel, are responsible for a number of epilepsy disorders including genetic epilepsy with febrile seizures plus (GEFS+) and Dravet syndrome (DS). Patients with SCN1A mutations often experience prolonged early-life febrile seizures (FSs), raising the possibility that these events may influence epileptogenesis and lead to more severe adult phenotypes. To test this hypothesis, we subjected 21-23-day-old mice expressing the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 90 publications
(109 reference statements)
2
48
0
Order By: Relevance
“…Although reliable data on seizure frequency during CIM use are not available for our cohort, increases in seizure frequency due to sodium channel blocker use have been reported previously . High seizure frequency has been associated with a worse cognitive outcome in Dravet syndrome patients, and similar findings have recently been shown in SCN1A + mice . Furthermore, if CIM is used, indicated medication is less likely to be prescribed, and therefore the negative effects of CIM can also partly be due to the deprivation of optimal treatment.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although reliable data on seizure frequency during CIM use are not available for our cohort, increases in seizure frequency due to sodium channel blocker use have been reported previously . High seizure frequency has been associated with a worse cognitive outcome in Dravet syndrome patients, and similar findings have recently been shown in SCN1A + mice . Furthermore, if CIM is used, indicated medication is less likely to be prescribed, and therefore the negative effects of CIM can also partly be due to the deprivation of optimal treatment.…”
Section: Discussionmentioning
confidence: 52%
“…6,27,28 High seizure frequency has been associated with a worse cognitive outcome in Dravet syndrome patients, 26,37 and similar findings have recently been shown in SCN1A+ mice. 38 Furthermore, if CIM is used, indicated medication is less likely to be prescribed, and therefore the negative effects of CIM can also partly be due to the deprivation of optimal treatment. It is therefore likely that an increased seizure severity, at least to some extent, explains the worse cognitive outcome associated with longer CIM use, in accordance with the epileptic encephalopathy disease model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that ELS protocols impair various behavioural domains, including memory; incidentally, ELS effects are generally much more prominent in male than in female rodents, which is one of the reasons why we restricted the present study to male mice only. Likewise, HT‐induced seizures affect memory performance later in life, although the results so far were somewhat equivocal . Most likely, the combination will have impact on behaviour, although this assumption clearly requires dedicated experiments to be substantiated.…”
Section: Discussionmentioning
confidence: 99%
“…40 Briefly, mice were placed in a plexiglass chamber (13.5 × 8 × 6 inches), and exposed to flurothyl (bis[2,2,2-trifluoroethyl] ether, Sigma-Aldrich) at a rate of 20 µL/min. 40 Briefly, mice were placed in a plexiglass chamber (13.5 × 8 × 6 inches), and exposed to flurothyl (bis[2,2,2-trifluoroethyl] ether, Sigma-Aldrich) at a rate of 20 µL/min.…”
Section: Flurothyl-induced Seizuresmentioning
confidence: 99%
“…Thresholds to flurothyl-induced seizures were determined as previously described. 40 Briefly, mice were placed in a plexiglass chamber (13.5 × 8 × 6 inches), and exposed to flurothyl (bis[2,2,2-trifluoroethyl] ether, Sigma-Aldrich) at a rate of 20 µL/min. Latencies to the first MJ and GTCS were recorded (n = 8-12/group).…”
Section: Flurothyl-induced Seizuresmentioning
confidence: 99%